Unveiling the Burden of Osteoporosis: Exploring the Prevalence and Risk Factors among Postmenopausal Women in North Central Bangladesh. - Kha, Md Salehin; Kibria, Md Golam; Hossain, Farhana; Ferdous, Jannatul; Shihab, Hossain Mohammad; Faisal, Shah Mohammad (Central Medical College Journal, 2024)
Background: Osteoporosis affects 30% of women globally between the ages of 40 and 50. This disease is among the top causes of death and disability among the elderly. This study aimed to examine the prevalence of primary osteoporosis and poor bone density in postmenopausal women, as well as their socio demographic, obstetric, and lifestyle risk factors. Aim: The purpose of this study is to investigate at the prevalence of osteoporosis and the risk factors linked with it in postmenopausal women. Methods: The present prospective cross-sectional study was conducted on postmenopausal women who visited orthopedics, gynecology, and medicine outpatient departments between August 2022 and March 2023; 539 women aged 45 to 80 years with verified menopause were recruited. The final recommendation was for 539 women to have bone mineral density testing utilizing dual energy X-ray absorptiometry. Socio-individual, obstetric-medical, short-form physical activity, and anthropometric questionnaires were administered. Chi-square and Student's t-tests were applied to categorical and continuous data, respectively, to assess the differences between the groups. In SPSS 26, P<0.05 was regarded to indicate significant connections. Results: In our study, 38.0% of participants were between 56 and 60 years of age. The majority of the individuals (51.9%) were illiterate. 37.7% of respondents reported having six or more children. 3.6% of the sample smoked or chewed tobacco. 61.0 percent of individuals had menopause after the age of 45, and 48.8% of subjects had experienced menopause for more than ten years at the time of enrollment in the research. 83.5% of postmenopausal women were affected by osteoporotic fractures (osteoporosis: 40.0% and osteopenia: 43.5%). The incidence of osteoporosis rose as parity and abortion rates increased. The prevalence of osteoporosis was greater (P< 0.05) among those with a familial history of osteoporosis-related symptoms and fragility fracture, as well as a personal history of fragility fracture. Conclusion: Given the significant prevalence of primary osteoporosis and poor bone density in postmenopausal women, health education is essential for minimizing modifiable risk factors and mitigating the disease's consequences. Central Medical College Journal Vol 7 No 1 January 2023 Page: 32-40